Formulating Institutional Harmonization of UNNES Legal Entity Organs in The Frame of Check and Balances System - Ali Masyhar; Siti Mursidah; Ali Murtadho (Universitas Negeri Semarang, 2023)
As a dynamic organization, Universitas Negeri Semarang (UNNES) continues to improve itself towards better public services, namely as a State University Legal Entity. State University Legal Entities have a very positive impact, especially the autonomy of academic and non-academic administration and management. After drafting the statutes and forming the organs of the UNNES, the institutions that need to be prepared are institutional arrangements so that the harmony of the organs of UNNES is maintained as a State University Legal Entity. In order to be organized and harmonious relations occur, in line between the organs of the UNNES as a state university legal entity, a check and balances system needs to be implemented. The application of checks and balances system between organs of State Universities Legal entities, UNNES needs to be covered in a regulation so that there will be no mutual claims and shows of strength. Based on this background, this research is based on the formulation of the problem, what is the format of the check and balances system of relations between organs of State University Legal Entities, UNNES in order to achieve the vision and mission as formulated in the statutes? And what is the appropriate formulation/draft so that there can be harmonization of relations between the organs of UNNES, State Universities Legal Entities? Based on the formulation of the problem, it is intended to produce a harmonious relationship format between organs of State Universities Legal Entities, UNNES, as well as produce appropriate regulations in maintaining harmonization of relations between organs of UNNES as a State Universities Legal Entity. Based on the research objectives, the suitable research method used is qualitative research with a policy approach. The research object is using deep interview and document analysis methods.